1989
DOI: 10.1111/j.1365-2826.1989.tb00127.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunoreactive Prolactin in the Cerebrospinal Fluid of Estrogen‐Treated and Lactating Rats as Determined by Push‐pull Perfusion of the Lateral Ventricles

Abstract: lmmunoreactive (ir) prolactin levels in the cerebrospinal fluid were measured in push-pull perfusion samples collected from the lateral cerebral ventricles in freely-moving ovariectomized rats prior to and after estrogen treatment, and in rats during pregnancy and lactation. Ir-prolactin levels in cerebrospinal fluid were elevated throughout the perfusion period in ovariectomized animals given estrogen and in Day 8 lactating females following the onset of nursing by their young. Cerebrospinal fluid perfusates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
7
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…A blood-to-CSF transport mechanism located in the cho roid plexus represents one possible route of access to such periventricular sites. This possibility is supported by evidence for PRL binding sites in the CP or ring doves [40] and a variety of other vertebrate species [41 ], by evi dence for concordance between changes in serum PRL concentrations and changes in C'SF level of PRL under some natural and experimental conditions [42][43][44], and by direct evidence for saturable uptake of radiolabelled PRL from blood to CSF in rats [45]. In an earlier study, intravenous injection of oPRL was found to be effective in inhibiting the uptake of radiolabelled oPRL in the dove CP at 5 min postinjeqtion [40].…”
Section: Discussionmentioning
confidence: 69%
“…A blood-to-CSF transport mechanism located in the cho roid plexus represents one possible route of access to such periventricular sites. This possibility is supported by evidence for PRL binding sites in the CP or ring doves [40] and a variety of other vertebrate species [41 ], by evi dence for concordance between changes in serum PRL concentrations and changes in C'SF level of PRL under some natural and experimental conditions [42][43][44], and by direct evidence for saturable uptake of radiolabelled PRL from blood to CSF in rats [45]. In an earlier study, intravenous injection of oPRL was found to be effective in inhibiting the uptake of radiolabelled oPRL in the dove CP at 5 min postinjeqtion [40].…”
Section: Discussionmentioning
confidence: 69%
“…Evidence increases in blood and CSF PRL levels in the mother rats (13). CSF PRL concentrations are also higher at times of the reproductive cycle when females exhibit elevations in circulating PRL (11,12).…”
mentioning
confidence: 90%
“…Interestingly, CSF concentrations of immunoreactive PRL are undetectable just prior to parturition (13). One possible explanation to account for the lack of PRL in the CSF at this time is that the high levels of rat placental lactogen II prepartum (9) (30,31) and estrogen receptors (32,33) in the MPOA prepartum may help stimulate the onset of maternal behavior.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…the MPOA. It was somewhat surprising to be unable to detect mitogenic activity in CSF samples obtained from lactating rats, since the suckling stimuli received by the dams induce large increases in cir culating PRL secretion [24,25] and increased immunoreactive PRL concentrations in CSF [26]. One explanation for the apparent lack of mitogenic activity in the CSF of lactating rats in the present study is that transport of PRL into the CSF from plasma reduces the biological activity of the PRL molecule without affecting its immunologic activity in the PRL radioimmunoassay.…”
Section: Discussionmentioning
confidence: 99%